Kartu bangun ruang sisi datar berbasis augmented reality - Abang Aldi Faghrudin; marhadi saputro; Hartono Hartono (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
This study discussed the development of learning media for material bangun ruang sisi datar yang berbasis Augmented Reality. Augmented Reality was a technology that combined 2D or 3D virtual objects into a real object. This study aimed to produce media Kartu Bangun Ruang Sisi Datar Berbasis   Augmented Reality which aimed to see the validity, practicality, and effectiveness of the media in the learning process of eighth-grade students of SMP Negeri 10 Sungai Kakap and to assist students in learning mathematics on the material media Kartu Bangun Ruang Sisi Datar berbasis Agumented Reality.This study uses the ADDIE development design model, which consists of five main stages, namely, analysis design, development, implementation, and evaluation. The subjects in this study were class VIII SMP Negeri 10 Sungai Kakap as many as 15 students. To see the validity, practicality, and effectiveness of the instruments used are validation sheets, questionnaires, and posttests. The result of research validity Media Kartu Bangun Ruang Sisi Datar Berbasis Augmented Reality, namely the average percentage value of the three experts of 89.25% with very valid criteria. For the value of practicality, it can be seen from the value of the questionnaire filled out by teachers and students which is accumulated so that a percentage of 81.57% is obtained with very practical criteria. Effectiveness, seen from student learning outcomes, the average obtained 80.66 already exceeds the school KKM, which is 70, so that the media kartu  bangun ruang sisi datar yang berbasis Augmented Reality was categorized as effective. In general, it can be concluded that the Media Kartu Bangun Ruang Sisi Datar Berbasis Augmented Reality  was valid, practical, and effective to use.